2016
DOI: 10.1371/journal.pone.0150658
|View full text |Cite
|
Sign up to set email alerts
|

Functional Stability of the Human Kappa Opioid Receptor Reconstituted in Nanodiscs Revealed by a Time-Resolved Scintillation Proximity Assay

Abstract: Long-term functional stability of isolated membrane proteins is crucial for many in vitro applications used to elucidate molecular mechanisms, and used for drug screening platforms in modern pharmaceutical industry. Compared to soluble proteins, the understanding at the molecular level of membrane proteins remains a challenge. This is partly due to the difficulty to isolate and simultaneously maintain their structural and functional stability, because of their hydrophobic nature. Here we show, how scintillatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Second, short synthetic peptides can have limited structure similarity with the native target. A potential approach that would use larger antigens but still allow for precision targeting would be to first immunize animals with the full-length protein positioned in a lipid system (e.g, nanodisc) and incorporate smaller peptide antigens during screening (47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…Second, short synthetic peptides can have limited structure similarity with the native target. A potential approach that would use larger antigens but still allow for precision targeting would be to first immunize animals with the full-length protein positioned in a lipid system (e.g, nanodisc) and incorporate smaller peptide antigens during screening (47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…The SPA assay was adapted from Hansen et al 34 . Briefly, 100 ng of AA2AR-nanodiscs, 100 ng of biotinylated-AA2AR purified in detergent, 60 ng of empty nanodiscs or 10 µg of membrane preparation samples were incubated in triplicates in 96well plates (ProxiPlate-96, Perkin Elmer) in presence of 10 µL of streptavidin-coated yttrium silicate SPA beads (Perkin Elmer) and 25 nM of [3H]-ZM241385 in 100 µL final volume of binding buffer (50 mM Tris-HCl pH 7.4, 10 mM MgCl2, 1 mM EDTA).…”
Section: Scintillation Proximity Assay (Spa)mentioning
confidence: 99%
“…MSP1E3D1) was in vitro biotinylated using a NHS-PEG4-Biotin reagent. While the resulting AA2AR nanodisc brings the receptor a stable membrane-mimicking environment compatible with an extensive use in dynamic conditions 34 , it also allows a strong immobilization on streptavidin-coated supports via the biotin residues grafted on the MSP belt. Thanks to the presence of the PEG spacer arm that further maintains the assembly at distance from the support, the overall particle design thus ensures a full accessibility of the extramembrane domains of the receptor to the solvent and to any potential ligands it may contains.…”
Section: Preparation Of Nanodiscs-embedded Aa2armentioning
confidence: 99%
“…Applying preparative procedures similar to those described in this article, a large number of these IMPs could then be extracted from P. pastoris membranes and isolated to quantity and quality levels compatible with their thorough characterization at the molecular level. A rapid, far from exhaustive, survey conducted on the last decade actually retrieved an abundance of information on a variety of IMPs produced in these conditions, covering screening and functional characterization of compounds (Wöhri et al 2013;Logez et al 2014;Scalise et al 2014;Dekki-Shalaly et al 2015;Zehnpfenning et al 2015;Zollmann et al 2015;Westh Hansen et al 2016;Igonet et al 2018), interactions with and regulation by proteins (Bornert et al 2014;Rosell et al 2014;Doshi et al 2017;Damian et al 2018) and lipids (Schölz et al 2011;Brohawn et al 2014), functional impact of critical mutations (Kapri-Pardes et al 2011;Ampah-Korsah et al 2017;Yang et al 2017;Christenson et al 2018), as well as structural insights and mechanistic details observed at the atomic level (Hino et al 2012;Kodan et al 2014;Fan et al 2011;Vinothkumar et al 2016;Wang et al 2016;Lolicato et al 2017;Deng et al 2018;Eddy et al 2018;Ye et al 2018;Garaeva et al 2019;Wang et al 2020).…”
Section: Background Informationmentioning
confidence: 99%
“…Similarly, specific activity assays are a mean of choice to evaluate the stability of IMP in solution. As an example, a time-resolved scintillation proximity assay was developed in a comparative analysis of the human kappa opioid receptor solubilized in various environment, showing that receptor stability was dramatically improved in nanodiscs compared to detergent (Westh Hansen et al 2016).…”
Section: Critical Parameters and Troubleshootingmentioning
confidence: 99%